Boosting Elementary Students' Mastery Of Passing Techniques: The Role Of Team Games Tournaments, Command Methods, And Learning Motivation - Ramadaniaty, Riri; Arsil, Arsil; Irawan, Roma; Syamsuar, Syamsuar; Ockta, Yovhandra; Sabilah, Muhamad Ichsan; Rahman, Dally (STKIP Singkawang, 2024)
The problem of this research is the low passing skills of futsal players of Elementary Schools 7 Pekanbaru. This study aims to find out: 1) The difference in the influence of the Teams Games Tournament (TGT) learning method and the command method on the improvement of the mastery of futsal passing techniques of Elementary Schools 7 Pekanbaru students, 2) The interaction between the TGT method and the command method is reviewed from the aspect of learning motivation on the improvement of the mastery of futsal passing techniques of Elementary Schools Negeri 7 Pekanbaru students, 3) The difference in the influence of the TGT learning method and the command method on mastery of futsal passing techniques of Elementary Schools 7 Pekanbaru students who have high learning motivation, 4) The difference in the influence of the TGT learning method and the command method on the mastery of futsal passing techniques of Elementary School 7 Pekanbaru students who have low learning motivation..This type of research is an experiment using a 2 x 2 factorial design. The population in this study is 38 students in grade V of Elementary Schools 7 Pekanbaru. The sample of this study amounted to 20 people who were taken using the purposive sampling technique, then ordinal pairing was carried out to divide the two groups. The instrument to measure learning motivation uses a questionnaire of the Likert skala, while passing uses the Vernon A Crew metode futsal passing test. The data analysis technique used is ANOVA two way.The results of the study were found: (1) There was a significant difference in the influence between the TGT method and the command method on the mastery of futsal passing for elementary school students. TGT method group is higher (good) compared to the command method learning group, 2) There is an interaction between the TGT learning method and the command learning method reviewed from the aspect of learning motivation (high and low) towards the improvement of futsal passing mastery of Elementary Schools 7 Pekanbaru students,with a value of F 5.333 and a significance value of p 0.035 < 0.05, 3) The difference in the influence of the TGT learning method and the command method on the mastery of futsal passing techniques of Elementary Schools 7 Pekanbaru students who have high learning motivation, 4) There is a difference in the influence of the TGT learning method and the command method on the mastery of futsal passing techniques of Elementary Schools 7 Pekanbaru students who have low learning motivation. Students who had high learning motivation were higher (good) compared to children who had low learning motivation, with an average posttest difference of 0.60